Kinematics analysis of cutting with dribbling during different approach speeds and cutting directions in soccer - Lo, T.-Y.; Yo, C.; Wu-Ye, C.; Huang, C.; Chang, J.-H. (International Journal of Performance Analysis in Sport, 2019)
We evaluated whether knees and hips are the key regions to anticipate an opponent`s cutting directions by using the kinematics method during different cutting tasks. Eighteen male university division 1 soccer players were the subjects of this study. Each participant was asked to cut with dribbling in four situations (2 speeds × 2 directions). The motion system and force platform were used synchronously to collect movements and ground reaction force during cutting with dribbling. The two-way repeated-measures analysis of variance was used for statistical analysis (a = .05). The knee external rotation angle of the non-pivot leg was greater when cutting to the non-dominant side at the event of the non-pivot leg toe-off and pivot leg landing. The hip extension/flexion angle of the non-pivot leg was different between directions and speeds at both events. The height difference between the anterior-superior iliac spines was greater at the pivot leg landing when cutting to the non-dominant side. This study might provide the evidence to support the visual search strategies for observing the regions of hip and knee to predict cutting direction. Therefore, defenders could focus on the motion of the pelvis, hip, and knee to anticipate the cutting motion in the match. KEYWORDS: Biomechanics, lower limb, football, joint angle, motion analysis